PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE, DAN BRANDTRUST TERHADAP REPURCHASE INTENTION (Studi pada Pelanggan Brotzeit Bali Bakery) - Ni Made Diah Putri Maharani; I Gde Ketut Warmika (BORJUIS: JURNAL OF ECONOMY, 2026)
The increasing competition in the bakery industry requires companies to develop effective social media marketing, establish a strong brand image, and enhance brand trust to encourage customers’ repurchase intention. The decline in sales experienced by Brotzeit Bali Bakery indicates problems related to factors influencing customers’ repurchase intention, thereby highlighting the need for further research.This study aims to analyze the influence of social media marketing, brand image, and brand trust on repurchase intention among Brotzeit Bali Bakery customers. This research employed a quantitative approach involving 160 respondents who were customers of Brotzeit Bali Bakery. The sampling technique used purposive sampling. Data were collected through questionnaires measured using a Likert scale to capture respondents’ perceptions of the research variables. The data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination.The results indicate that social media marketing, brand image, and brand trust have a positive and significant effect on repurchase intention among Brotzeit Bali Bakery customers, both partially and simultaneously. Therefore, these three variables are important factors in increasing customers’ repurchase intention at Brotzeit Bali Bakery.The implications of this study suggest that Brotzeit Bali Bakery should optimize creative and interactive social media marketing, maintain consistent product quality to strengthen brand image, and improve service and brand credibility to build brand trust. These integrated strategies are expected to enhance customers’ repurchase intention at Brotzeit Bali Bakery and support the sustainability of the company’s sales performance.